The Influence of Video Marketing, Live Streaming Commerce, and Sharia Belief on E-Commerce Purchasing Decisions (Glad2Glow Product Study in Sidoarjo) - Ani Faujiah; Qurrotul A'yuni (Institut Agama Islam Negeri (IAIN) Curup, 2026)
This study aims to analyze the contribution of Video Marketing Content, Live Streaming Commerce, and Sharia Consumer Trust in influencing Purchase Decisions of Glad2Glow products in Sidoarjo Regency. This study uses a quantitative approach with multiple linear regression methods, data collected through questionnaires from Glad2Glow product users and analyzed using classical assumption tests and hypothesis tests through the help of IBM SPSS Statistics 27 software. The results of the study indicate that partially, Video Marketing Content (t = 3.460), Live Streaming Commerce (t = 2.757), and Sharia Consumer Trust (t = 2.778) have a positive and significant effect on Purchase Decisions, with the Video Marketing Content variable as the most dominant factor. Simultaneously, the three variables have a significant effect (F = 53.596) with a coefficient of determination (R^2) of 62.3%, which indicates that the synergy between visual strategies and sharia ethical foundations is effective in minimizing uncertainty (gharar) and strengthening consumer transaction confidence. The originality of this research lies in the integration of Islamic economic values ​​into the dynamics of modern digital marketing in the cosmetics industry, which provides theoretical contributions to consumer behavior literature as well as practical insights for business actors in optimizing value-based sales strategies in the digital ecosystem.